2021
DOI: 10.46925//rdluz.34.31
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors and linguistic image in the analysis of phraseological units of the archaic Olonkho narrative

Abstract: The article analyzes metaphors in the linguistic image of the world using the description of the sky (айыы) and underground (абаасы), mythical creatures represented in phraseological units with numbers in T.V. Zakharov-Chääbij's Epic (2018) "Bulkun Wing the Hero". Compositional analysis, context analysis and the method of phraseological identification were used. The general method of investigation is induction-deduction, with theoretical conclusions drawn from the analysis of the material. The study of the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Also, it was shown that the emotive and sensonymic components of Tatar idioms is determined by Tatar history, culture and traditions (Khasanzyanova, 2018;Yahin et al, 2017;Sibgaeva et al, 2021); the same seems to be true for the Uzbek linguistic worldview (Yuldashev, 2020). According to the study of phraseological units with a numerical component in the Yakut language, these units describe the appearance of the heaven hero and the underground creature from the Olonkho (Zakharov et al, 2021). In Chinese, phraseological units with zoonyms reflect the roles of certain animals in the life of the Chinese ethnos (Daulet et al, 2019).…”
Section: Review Papermentioning
confidence: 99%
“…Also, it was shown that the emotive and sensonymic components of Tatar idioms is determined by Tatar history, culture and traditions (Khasanzyanova, 2018;Yahin et al, 2017;Sibgaeva et al, 2021); the same seems to be true for the Uzbek linguistic worldview (Yuldashev, 2020). According to the study of phraseological units with a numerical component in the Yakut language, these units describe the appearance of the heaven hero and the underground creature from the Olonkho (Zakharov et al, 2021). In Chinese, phraseological units with zoonyms reflect the roles of certain animals in the life of the Chinese ethnos (Daulet et al, 2019).…”
Section: Review Papermentioning
confidence: 99%